2014
DOI: 10.1590/1414-431x20143483
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced expression of functional surface molecules in regulatory and effector T cells in systemic lupus erythematosus

Abstract: Regulatory T (TREG) cells play an important role in maintaining immune tolerance and avoiding autoimmunity. We analyzed the expression of membrane molecules in TREG and effector T cells in systemic lupus erythematosus (SLE). TREG and effector T cells were analyzed for the expression of CTLA-4, PD1, CD28, CD95, GITR, HLA-DR, OX40, CD40L, and CD45RO in 26 patients with active disease, 31 with inactive disease, and 26 healthy controls. TREG cells were defined as CD25+/highCD127Ø/lowFoxP3+, and effector T cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Consistent with observations from conditions where there is [97][98][99][100][101][102][103] Increased endothelial expression in kidney biopsies from lupus nephritis patients with the appearance of glomerular positivity [97] OX40 on infiltrating perivascular leucocytes in lupus nephritis [97] Increased peripheral sOX40L, with further elevations in those with nephritis [99] More activated phenotype with increased PI3/Akt activation (see Fig. 4…”
Section: Ox40 Is Upregulated On Peripheral Circulating Lymphocytes Insupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with observations from conditions where there is [97][98][99][100][101][102][103] Increased endothelial expression in kidney biopsies from lupus nephritis patients with the appearance of glomerular positivity [97] OX40 on infiltrating perivascular leucocytes in lupus nephritis [97] Increased peripheral sOX40L, with further elevations in those with nephritis [99] More activated phenotype with increased PI3/Akt activation (see Fig. 4…”
Section: Ox40 Is Upregulated On Peripheral Circulating Lymphocytes Insupporting
confidence: 83%
“…in SLE [97][98][99][100][101][102][103]. Disease-ameliorating interventions can reduce proportions of circulating lymphocytes expressing OX40 such as natalizumab in multiple sclerosis or may correlate with other measures of severity: in myasthenia gravis there is a correlation with acetylcholine receptor antibody titer [104,105].…”
Section: Colitis Expression Increased On Lamina Propria Lymphocytes Imentioning
confidence: 99%
“…The investigation conducted by Mesquita et al ( 101 ) reported several alterations in the expression of critical surface molecules on Treg and Teff cells in 26 SLE patients with active disease compared to 31 with inactive disease and 26 healthy controls, despite healthy controls and SLE patients showed equivalent Treg cell frequency. More specifically, a higher CD40L + Treg cell frequency, associated with reduced CTLA-4 + Treg and CD28 + Treg cell frequencies, characterized SLE subjects.…”
Section: Evidences Of Pd-1 and Treg Involvement In Autoimmunitymentioning
confidence: 99%
“…The frequency of CD40L + Tregs was positively correlated with the SLE disease activity index. These alterations could play an important role in SLE pathogenesis ( 101 ).…”
Section: Evidences Of Pd-1 and Treg Involvement In Autoimmunitymentioning
confidence: 99%
“…In contrast, Tregs have also been shown to be significantly expanded in patients with active SLE compared to those with inactive disease and HCs ( 10 13 ). Some studies suggest that the defects of Tregs are secondary to the imbalance between auto-aggressive T-cells and Tregs in lupus patients, tipping the balance toward Teffector (Teff) activation, clonal expansion, cell survival, cytokine production, and ultimately, autoimmunity ( 8 , 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%